A passively mode-locked thulium-doped fiber laser based on a D-shaped fiber deposited with PbS nanoparticles. Issue 36 (2nd September 2019) - Zhou, Yong; Zhang, Zhengxiong; Jiang, Wenhui; Gao, Panyun; Zhang, Xiu; Zhang, Wei; Zhang, Ying; Qyyum, Abdul; Li, Xiaohui; Liao, Meisong; Gao, Weiqing
Abstract : A passively mode-locked thulium-doped fiber laser with ultra-fast pulse generation based on a D-shaped fiber deposited with PbS nanoparticles. Abstract : We demonstrate a passively mode-locked thulium-doped fiber laser through the utilization of PbS nanoparticles (NPs) with ultrafast pulse generation in this letter. The PbS NPs are deposited on a D-shaped fiber by the optical deposition method. The cavity shows a net dispersion of −0.781 ps 2 . The central wavelength of the output spectrum is at 1930 nm with a 3 dB bandwidth of 3.2 nm. The pulse repetition is 19.74 MHz with the duration of 1.3 ps. The time-bandwidth product is calculated to be 0.35. The second- and third-order harmonics are observed with the increase of pump power. The bound solitons are also observed in the cavity when the pump power is higher than ∼600 mW. The D-shaped fiber SA shows a damage threshold of higher than 3.5 kW. These results demonstrate that the PbS NPs are indeed an excellent material for passively mode locking in mid-infrared wavebands.